Individual muscle hypertrophy in high-load resistance training with and without blood flow restriction: A near-infrared spectroscopy approach - Bergamasco, J. G. A.; Bittencourt, D.; Silva, D. G.; de Campos Biazon, T. M. P.; Soligon, S. D.; Oliveira, R. M.; Libardi, C. A. (Journal of Sports Sciences, 2025)
We aimed to compare individual hypertrophic responses to high-load resistance training (HL-RT) or high-load with blood flow restriction (HL-BFR). Furthermore, we investigated whether greater responsiveness to one of the protocols could be explained by acute changes in blood deoxyhemoglobin concentration (HHb) and total hemoglobin concentration (tHb) (proxy markers of metabolic stress). Ten untrained participants had their legs randomized into both HL-RT and HL-BFR and underwent 10 weeks of training. Muscle cross-sectional area (mCSA) was measured at baseline and post training, while HHb and tHb during the final session. Using a threshold of 2 × typical errors (3.24%) to compare protocols, five participants showed greater mCSA increases after HL-RT (16.44 ± 7.90%) compared to HL-BFR (10.74 ± 7.12%, p = 0.0054) and five did not respond better to HL-RT (8.95 ± 10.83%) compared to HL-BFR (13.33 ± 8.59%) (p = 0.3105). Additionally, HL-RT induced lower HHb (5855.78 ± 12905.99; p = 0.0101) and tHb (-43169.70 ± 37793.17; p = 0.0030) AUC values compared to HL-BFR (HHb: 39254.80 ± 27020.15; tHb: 46309.40 ± 31613.97). In conclusion, despite the higher levels of metabolic stress markers, most participants did not present greater muscle hypertrophy by combining blood flow restriction with HL-RT.